2009
DOI: 10.1080/15563650902724813
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac abnormalities in acute organophosphate poisoning

Abstract: Patchy myocardial involvement as a result of direct cardiac toxicity could be one of the factors responsible for serious cardiac complications. As myocardial involvement is patchy, it may not be manifest clinically or on echocardiography. Continuous cardiac monitoring should be undertaken to detect dynamic cardiac changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 18 publications
1
52
0
Order By: Relevance
“…Myocardial blotchiness, patchy pericarditis, subepicardial hemorrhage, and hemorrhages on the posterior aspect of the left ventricle and left atrium were observed in three cases. The authors attributed this to early myocardial toxicity, although some of these changes could have been due to attempted CPR [16].…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial blotchiness, patchy pericarditis, subepicardial hemorrhage, and hemorrhages on the posterior aspect of the left ventricle and left atrium were observed in three cases. The authors attributed this to early myocardial toxicity, although some of these changes could have been due to attempted CPR [16].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated ST segment was seen in 25.2% patients. 17 The limitation of our study is that the final outcome of patients was not observed as it was not the aim of our study.…”
Section: Discussionmentioning
confidence: 99%
“…279À281 Late-onset arrhythmias may represent healing myocardium or increased free fatty acid levels in the myocardium. 276,280,287 Poor prognostic factors include a combination of ST segment and T-wave changes with concomitant low-voltage complexes. 276 It is difficult to predict which patients are likely to develop the cardiac manifestations of organophosphate poisoning and when after exposure these toxicities may manifest.…”
Section: Organophosphatesmentioning
confidence: 99%